Association between sarcoidosis and HLA polymorphisms in a Czech population from Central Europe: focus on a relationship with clinical outcome and treatment - Sikorova, K.; Osoegawa, K.; Kocourkova, L.; Strnad, A.; Petrkova, J.; Fernández-Viña, M. A.; Doubkova, M.; Petrek, M. (Frontiers in Medicine, 2023)
Background: Sarcoidosis is an immune-mediated systemic disease with unknown etiology affecting the lung predominantly. The clinical manifestation of sarcoidosis is rather diverse ranging from Löfgren's syndrome to fibrotic disease. Also, it differs among patients with distinct geographical and ethnic origins, consistent with environmental and genetic factors' role in its pathogenesis. Of those, the polymorphic genes of the HLA system have been previously implicated in sarcoidosis. Therefore, we have performed an association study in a well-defined cohort of Czech patients aiming to define how variation in HLA genes, may contribute to disease origin and development. Materials and methods: 301 Czech unrelated sarcoidosis patients were diagnosed according to international guidelines. In those, HLA typing was performed using next-generation sequencing. The allele frequencies at six HLA loci (HLA-A,-B,-C,-DRB1,-DQA1,-DQB1) observed in the patients were compared with HLA allele distribution determined in 309 unrelated healthy Czech subjects; sub-analyses of relationships between HLA and distinct sarcoidosis clinical phenotypes were performed. Associations were assessed by two-tailed Fischer's exact test with correction for multiple comparisons. Results: We report two variants, HLA-DQB1*06:02, and HLA-DQB1*06:04, as risk factors for sarcoidosis, and three variants, HLA-DRB1*01:01, HLA-DQA1*03:01, and HLA-DQB1*03:02 as protective factors. HLA-B*08:01, HLA-C*07:01, HLA-DRB1*03:01, HLA-DQA1*05:01, and HLA-DQB1*02:01 variants associated with Löfgren's syndrome, a more benign phenotype. HLA-DRB1*03:01 and HLA-DQA1*05:01 alleles were connected with better prognosis – chest X-ray (CXR) stage 1, disease remission, and non-requirement of corticosteroid treatment. The alleles HLA-DRB1*11:01 and HLA-DQA1*05:05 are associated with more advanced disease represented by the CXR stages 2-4. HLA-DQB1*05:03 associated with sarcoidosis extrapulmonary manifestation. Conclusion: In our Czech cohort, we document some associations between sarcoidosis and HLA previously described in other populations. Further, we suggest novel susceptibility factors for sarcoidosis, such as HLA-DQB1*06:04, and characterize associations between HLA and sarcoidosis clinical phenotypes in Czech patients. Our study also extends the role of the 8.1 ancestral haplotype (HLA-A*01:01, HLA-B*08:01, HLA-C*07:01, HLA-DRB1*03:01, HLA-DQA1*05:01, and HLA-DQB1*02:01), already implicated in autoimmune diseases, as a possible predictor of better prognosis in sarcoidosis. The general translational application of our newly reported findings for personalized patient care should be validated by an independent study from another, international referral center.